Community Social Work Guided by a Psychodynamic Approach in the Community of Long-Term Israelis Aged 60 and Above - Keini, Noga Levin; Helper, Amit (Advances in Social Sciences Research Journal, 2026)
The strengths and advantages of the psychodynamic approach in community social work include the ability to provide insights into complex emotional situations, the enhancement of community self-awareness, and the empowerment of change processes. Social work guided by this approach will focus on understanding the psychological forces at play within the community, while utilizing the principles of dynamic therapy to achieve deep and lasting change. In this article, we will propose an activity framework that combines community social work with the psychodynamic approach aimed at veteran Israelis, although this framework also allows for community activities targeting various and diverse populations.